'Homoeopathy flourishes in the far East': A forgotten history of homeopathy in late nineteenth-century China. (19th September 2018) - Lu, Di
Abstract : Homeopathy and its transnational transmission have received significant attention from historians of medicine. But the emergence of homeopathy in modern Chinese society has remained little explored. This article identifies the homeopathic practitioners arriving in nineteenth-century China, and then explores their origins, efforts and sense of professional identity in a transnational context. The history of homeopathy in China is found to begin in the late nineteenth century, during which the growth of the Christian missionary enterprise promoted the arrival of sporadic Euro-American homeopathic practitioners, also missionaries, in coastal regions of China. Almost all of them received professional training in American homeopathic medical institutions; and most of them were females, providing additional opportunities for local women patients to receive treatment. The practitioners recognized homeopathy and their collective homeopathic identity, but their healing services were not necessarily essentially homeopathic. Homeopathy that they learnt also evolved and transacted with exotic knowledge during its globalization. Under the influence of homeopathy, some Euro-Americans claimed to have discovered homeopathic elements in Chinese medical ideas and practice. The early history of homeopathy explored in this article helps deconstruct the popular imagination of a coherent 'Western medicine' in modern China.